Atributos químicos do solo e produtividade do milho afetados por corretivos e manejo do solo - Santos, José R.; Bicudo, Silvio José [UNESP]; Nakagawa, João [UNESP]; De Albuquerque, Abel W.; Cardoso, Celso L. [UNESP] (FapUNIFESP (SciELO), 2006)
A field experiment was carried out in the Lageado Experimental Farm belonging to the São Paulo State University - UNESP, Campus of Botucatu, SP, in a distrophic Nitosoil in 1997/98. The objective was to compare the effects of magnesium termophosphate; termophosphate + lime; termophosphate + phosphogypsum + sugarcane vinnace application on the chemical characteristics of the soil and on the corn (Zea mays L.) yield cultivated in no-tillage and conventional tillage systems. The Crotalaria juncea was cultivated as mulch-producing to make possible the establishment of the tillage systems. The mean modifications in the soil fertility were due to aplication of the magnesium termophosphate. The differences between the two tillage systems, related to crop productivity, were associated to the smaller N content in the corn leaf in the no-tillage system.
Chemical properties of soil and productivity of corn affected by amendments and soil management
Keywords: Conventional tillage; Liming; Magnesium termophosphate; No-tillage; Sugarcane vinnace; Crotalaria; Crotalaria juncea; Phosphogypsum; Zea mays